Implementasi Orhiba Di Mahad Al-Zaytun Pada Masa Pandemi Covid-19 - Sobirin Sobirin; Budi Santoso (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The Corona Virus Disease outbreak, also known as the Corona virus or Covid-19, is an acute respiratory syndrome disease that has spread to nearly every country in the world, infecting and killing many people. Education is one aspect of life that has been affected by this epidemic. The Indonesian government enforces online or online learning to prevent transmission. Nonetheless, an educational institution known as the Al Zaytun Campus continues to provide face-to-face instruction while adhering to health protocols and implementing numerous innovations. The innovations implemented are referred to as ORHIBA (New Life Order). The topic of this paper is therefore "ORHIBA Implementation at Mahad Al Zaitun During the Covid-19 Pandemic." Using a phenomenological research methodology, this study aims to determine how ORHIBA is implemented on the Al Zaytun campus. From the research findings, it was determined that there were changes to a healthier lifestyle than usual, while still adhering to WHO health standards in handling Covid-19, in addition to a number of innovations in various sectors that produced better results. It is hoped that this way of life will serve as a model for other locations, including the government, which is presently implementing the New Normal way of life.Keywords: Strategy; ORHIBA; Covid-19 Pandemic AbstrakWabah Penyakit Virus Corona, juga dikenal sebagai virus Corona atau Covid-19, adalah penyakit sindrom pernafasan akut yang telah menyebar ke hampir setiap negara di dunia, menginfeksi dan membunuh banyak orang. Pendidikan merupakan salah satu aspek kehidupan yang terkena imbas dari wabah ini. Pemerintah Indonesia memberlakukan pembelajaran daring atau online untuk mencegah penularan. Meski demikian, lembaga pendidikan yang dikenal dengan nama Kampus Al Zaytun ini tetap memberikan pengajaran tatap muka dengan tetap mematuhi protokol kesehatan dan menerapkan berbagai inovasi. Inovasi yang diterapkan disebut sebagai ORHIBA (Tatanan Hidup Baru). Makalah ini diangkat dengan topik “Implementasi ORHIBA di Mahad Al Zaitun Selama Pandemi Covid-19”. Dengan menggunakan metodologi penelitian fenomenologi, penelitian ini bertujuan untuk mengetahui bagaimana implementasi ORHIBA di kampus Al Zaytun. Dari hasil penelitian diketahui adanya perubahan pola hidup yang lebih sehat dari biasanya, dengan tetap berpegang pada standar kesehatan WHO dalam penanganan Covid-19, selain sejumlah inovasi di berbagai sektor yang membuahkan hasil lebih baik. Cara hidup seperti ini diharapkan dapat menjadi percontohan bagi daerah lain, termasuk pemerintah yang saat ini menerapkan cara hidup New Normal.Kata Kunci: Strategi; ORHIBA; Pandemi Covid-19